Effect of fluorine substitution and position on phenylene spacer in carbazole based organic sensitizers for dye sensitized solar cells. Issue 42 (23rd October 2017) - Adil Afroz, Mohammad; Sonigara, Keval K.; Bhim Raju, Telugu; Soni, Saurabh S.; Krishnan Iyer, Parameswar
Abstract : The study on specific positions of fluorine substitution on phenylene spacer in organic dyes illustrated that ortho -substitution resulted in the improved power conversion efficiency of >4%. Abstract : The preparation of a series of organic dyes having a carbazole donor, cyanoacrylic acid as an acceptor, and phenylene ring as a spacer with the difference in the positions of fluorine substitution is reported. Due to its unique properties of small size and high electronegativity, fluorine is now being extensively used to control the optoelectronic properties of organic conjugated materials. In this study, the results revealed that the specific position and number of fluorine substitution were very crucial to control the optical as well as the electrochemical properties of organic dyes. It was found that fluorine substitution led to a redshift in the absorption spectra of the dyes and reduced the band gap. The injection rate of photoexcited electrons was measured using time-resolved photoluminescence and the o -fluoro substituted dyeMA1F-o showed the best electron injection dynamics. As a result of broad absorption and high electron injection rate, the dyeMA1F-o outperformed other dyes with a power conversion efficiency of 4.02% ( J sc = 8.3 mA cm −2, V oc = 0.75 V and FF = 0.64). The non-fluorinated dyeMA0F exhibited a power conversion efficiency of 3.23% ( J sc = 6.8, V oc = 0.72 and FF = 0.67). The dyeMA1F-m exhibited the least molar absorption coefficient and a lower power conversion efficiency because of the meta inductive effect.